THE USE OF ELECTRONOIC U-DICTIONARY TO IMPROVE NON-ENGLISH STUDENTS' VOCABULARY MASTERY AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Azhar, Ahmad; ul Haq, Muhammad Zia; Sulkifli (FKIP Unismuh Makassar, 2021)
This thesis aims at finding out whether or not the use of Electronic U-Dictionary effective to improve non English students’ vocabulary mastery. This research is pre-experimental research with pre-test and post-test design. The pretest was given before giving treatment and the posttest was given after giving treatment. The population of the research was the fourth semester students of PGSD Study Program in Muhammadiyah University of Makassar academic year 2022-2023. There are thirteen classes where each class consist of 25 students, so the sum of the population is 325. The sampling technique used is cluster random sampling. The researcher used one class as the sample which contained 25 students. To get the data, the researcher used vocabulary test as the instrument. The data were then analyzed by using SPSS. The results of the statistical analysis shows that the mean score of the pre-test is 53,5 and post-test is 81,6. The result of P=0.00 while α=0.05. it could be that α is higher than P with degree of freedom (df) = 25-1 = 24. Therefore, the alternative hypothesis (H1) is accepted and null hypothesis (H0) rejected. Based on analysis of the result, it could be summed up that the use of Electronic U-Dictionary is effective in teaching vocabulary.